An efficient and label-free LC-MS/MS method for assessing drug's activity at dopamine and serotonin transporters using transporter-transfected HEK293T cells. (June 2021) - Lin, Zebin; Liu, Chenyang; Fan, Enshan; Zhang, Yurong; Zheng, Shuiqing; Rao, Yulan
Background: Dopamine transporter (DAT) and serotonin transporter (SERT) are targets for many psychoactive substances. Functional assays including uptake inhibition and release assays often involve radiolabeled compounds like [ 3 H]-dopamine and [ 3 H]-serotonin to assess drug activity at transporters, which have high requirements on handling radioactive samples. Aims: The aim of this study was to establish a label-free method to assess drug activity at DAT and SERT. Methods: A liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) method was established using transporter-transfected human embryonic kidney 293T (HEK293T) cells. This method was evaluated by testing the effects of amphetamine and cocaine in the assay procedure. Results: The limits of detection of this method were 0.2 nM for both dopamine (DA) and serotonin (5-HT), with good linearities in the range of 0.5–160 nM. Amphetamine and cocaine's IC50 and EC50 on DAT and SERT determined by this method were consistent with previous reports. Conclusions: A rapid, reliable and label-free LC-MS/MS method for assessing drug activity was established, which affords an attractive alternative for those laboratories that do not have a radiation license or capabilities.